Facile Preparation and Characteristic Analysis of Sulfated Cellulose Nanofibril via the Pretreatment of Sulfamic Acid-Glycerol Based Deep Eutectic Solvents - Weidong Li (MDPI AG, 2021)
A deep eutectic solvent (DES) composed of sulfamic acid and glycerol allowed for the sustainable preparation of cellulose nanofibrils (CNF) with simultaneous sulfation. The reaction time and the levels of sulfamic acid demonstrated that fibers could be swelled and sulfated simultaneously by a sulfamic acid-glycerol-based DES and swelling also promoted sulfation with a high degree of substitution (0.12). The DES-pretreated fibers were further nanofibrillated by a grinder producing CNF with diameters from 10 nm to 25 nm. The crystallinity ranged from 53–62%, and CNF maintained the original crystal structure. DES pretreatment facilitated cellulose nano-fibrillation and reduced the energy consumption with a maximum reduction of 35%. The films prepared from polyvinyl alcohol (PVA) and CNF showed good UV resistance ability and mechanical properties. This facile and efficient method provided a more sustainable strategy for the swelling, functionalization and nano-fibrillation of cellulose, expanding its application to UV-blocking materials and related fields.